2017
DOI: 10.1212/wnl.0000000000003808
|View full text |Cite
|
Sign up to set email alerts
|

Diverging white matter trajectories in children after traumatic brain injury

Abstract: Objective: To examine longitudinal trajectories of white matter organization in pediatric moderate/severe traumatic brain injury (msTBI) over a 12-month period.Methods: We studied 21 children (16 M/5 F) with msTBI, assessed 2-5 months postinjury and again 13-19 months postinjury, as well as 20 well-matched healthy control children. We assessed corpus callosum function through interhemispheric transfer time (IHTT), measured using event-related potentials, and related this to diffusion-weighted MRI measures of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 32 publications
(53 reference statements)
2
35
1
Order By: Relevance
“…Overall, we observed decreased AD in acute patients versus controls, which we ascribed to acute axonal damage and cytotoxic oedema following inflammation [11]; we found increased AD in chronic patients, attributable to secondary degeneration [5]. Chronic patients showed decreased FA and increased diffusivities in the CC.…”
Section: Discussionmentioning
confidence: 53%
“…Overall, we observed decreased AD in acute patients versus controls, which we ascribed to acute axonal damage and cytotoxic oedema following inflammation [11]; we found increased AD in chronic patients, attributable to secondary degeneration [5]. Chronic patients showed decreased FA and increased diffusivities in the CC.…”
Section: Discussionmentioning
confidence: 53%
“…In prior papers we have shown that a subgroup of pediatric msTBI patients experiences a progressive decrease in WM organization (Dennis, 2017b). However, with only dMRI data, we were not able to determine whether these deficits were due to demyelination, inflammation, or other changes in neuronal organization.…”
Section: Discussionmentioning
confidence: 95%
“…In the first few months post-injury, some msTBI patients have significantly impaired callosal functional and structural integrity, and this affects cognitive performance as well. Additionally, these differences appear to be progressive, as one subgroup experiences expanding WM disruption and atrophy while the other subgroup of msTBI children appears to begin to return to a healthy trajectory (Dennis, 2017a; Dennis, 2017b). Importantly, the subgroup with impaired callosal function does not differ from the other msTBI patients in demographic or acute injury variables (including the incidence of lesions as detected by acute CT).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dennis et al did not find a significant effect of age or severity, but found two subgroups of patients based on post-acute interhemispheric transfer time (IHTT). Those patients with significantly slower IHTT than healthy controls showed progressive decline in WM organization over time, while those with IHTTs within the healthy control range showed evidence of recovery [30]. Several studies have examined how dMRI measures in the acute or post-acute phase can predict chronic outcome.…”
Section: Moderate-severe Brain Injurymentioning
confidence: 99%